RELIEF MAPPING OF THE FERGHANA VALLEY USING SLOPE AND GIS PROGRAMS (Scientific journal of the Fergana State University, 2024)
The article provides important information about the importance of studying the slope of the relief and methods for mapping it. Also with separate descriptions is the sequence of work on mapping the slope of the terrain using GIS programs. At the end of the work, a map of the relief slopes of the Fergana Valley territory was developed and a table of morphometric indicators was generated accordingly.